2021
DOI: 10.3390/ijerph18094907
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cardiac Rhabdomyomas with mTOR Inhibitors in Children with Tuberous Sclerosis Complex—A Systematic Review

Abstract: Background: Cardiac rhabdomyomas (CRs) are the earliest sign of tuberous sclerosis complex (TSC). Most of them spontaneously regress after birth. However, multiple and/or large tumors may result in heart failure or cardiac arrhythmia. Recently, the attempts to treat CRs with mTOR inhibitors (mTORi) have been undertaken. We reviewed the current data regarding the effectiveness and safety of mTORi in the treatment of CRs in children with TSC. Methods: The review was conducted according to the PRISMA guidelines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…Despite the generally favorable outcomes and spontaneous regression, multiple or large cRHMs may result in heart failure or cardiac arrhythmias that require intervention. A meta-analysis summarized the use of mTOR inhibitors in the treatment of cRHM in pediatric patients, most of which were neonates [ 7 ]. It reported that the clinical symptoms improved in 90.9% of patients after treatment and the size of cRHM was reduced by 95.1%.…”
Section: Mtor Inhibitors In the Treatment Of Tscmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the generally favorable outcomes and spontaneous regression, multiple or large cRHMs may result in heart failure or cardiac arrhythmias that require intervention. A meta-analysis summarized the use of mTOR inhibitors in the treatment of cRHM in pediatric patients, most of which were neonates [ 7 ]. It reported that the clinical symptoms improved in 90.9% of patients after treatment and the size of cRHM was reduced by 95.1%.…”
Section: Mtor Inhibitors In the Treatment Of Tscmentioning
confidence: 99%
“…Cardiac rhabdomyoma (cRHM) is a common benign cardiac tumor in patients with TSC that is found in 90% of intrauterine fetuses; Unlike other TSC symptoms, most cRHMs subside spontaneously in early childhood [ 3 ]. However, it may also re-grow or occur de novo in adolescence, especially in girls [ 7 ]. Generally, approximately 20% adults still carried cRHM.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is no approved pharmacological treatment for this condition, and cardiac surgery is the usual treatment for severe symptomatic patients. 45 , 46 The upcoming randomized trial assessing the efficacy of everolimus as a specific therapy for symptomatic cardiac rhabdomyoma (ORACLE) will potentially support the first evidence-based therapy for this condition. 46 , 47 …”
Section: Clinical Features and Their Managementmentioning
confidence: 99%
“… 45 , 46 The upcoming randomized trial assessing the efficacy of everolimus as a specific therapy for symptomatic cardiac rhabdomyoma (ORACLE) will potentially support the first evidence-based therapy for this condition. 46 , 47 …”
Section: Clinical Features and Their Managementmentioning
confidence: 99%
“…The effectiveness of oral mTOR inhibitors for the treatment of TSC-related manifestations is established for subependymal giant cell astrocytoma (SEGA), renal angiomyolipoma, lymphangioleiomyomatosis (LAM), epilepsy, cardiac rhabdomyoma, and skin lesions [10][11][12][13][14][15]. However, oral mTOR inhibitors are not approved by regulators for treatment of facial angiofibroma as there could be increased risk of systemic side effects associated with an immunosuppressive effect of these drugs.…”
Section: Introductionmentioning
confidence: 99%